A novel wide-range continuously-tuneable varactor-based matching network for low-noise amplifiers. Issue 1 (2nd January 2016) - Guan, Yangyang; Wu, Yongle; Zhang, Xiaoliang; Liu, Yuanan
Abstract : With the increasing demand of wideband or multi-standard wireless communications, low-noise amplifiers (LNAs) with wideband characteristics have become a crucial building block of typical receivers. In the design of LNAs, the major parameters such as gain, return loss and noise figure (NF) heavily rely on the input and output matching. In this paper, a novel tuneable matching network is proposed and a wide-range tuneable LNA operating within the range from 1.5 GHz to 2.3 GHz is constructed with this novel matching network. The capacity of this proposed matching structure to be continuously-tuneable is accomplished by utilising varactors of which the capacitance can be optionally controlled. Furthermore, the design theory of the proposed tuneable matching network is derived. A microstrip prototype of the LNA is simulated, fabricated and measured for verification. The LNA prototype maintains gain and return loss over 10 dB in the frequency range from 1.5 GHz to 2.3 GHz. Additionally, all operating-frequency NFs of the prototype are below 3 dB. The measured results show that the performance of the fabricated prototype is consistent with the simulation, which demonstrates the effectiveness of this proposed new design.